Phytoseiid mites (Acari: Phytoseiidae) of the Dominican Republic, with a re-definition of the genus Typhloseiopsis De Leon - Ferragut, Francisco; de Moraes, Gilberto Jose; Navia, Denise (Zootaxa, 2011)
The phytoseiid mites of the Dominican Republic are virtually unknown. In a survey conducted in areas of natural vegetation of that country, 23 species were collected, two of which, Phytoseius dominicensis Ferragut & Moraes sp. nov. and Typhloseiopsis adventitius Ferragut & Moraes sp. nov., are new to science. We report the species found in that survey, describe the two new species, and provide complementary morphological information about other species. To accommodate the new Typhloseiopsis De Leon species, a redefinition of Typhloseiopsis is proposed. A key for the separation of the species in this genus is provided.